Is the Digital Divide Inhibiting Urban Energy Transitions?—Evidence from China - Zhilun Jiao; Zixuan Xia (Energies)
The swift advancement of information technology has significantly impacted the energy transition. Being the largest energy consumer globally, China’s acceleration of the urban energy transition will promote sustainable development and pave the way for future development. This study examines the impact of the digital divide between cities regarding the energy transition by using panel data for 271 Chinese cities from 2006 to 2021. We found the following results. (1) The digital divide has an inhibitory effect on the energy transition of cities, hindering their development towards green and low-carbon development. (2) Further analyses found that the negative impact of the digital divide on energy transition can be effectively mitigated by strengthening urban infrastructure construction, promoting emerging technological innovation, and cultivating and attracting talent in the digital industry. (3) The results of the subsample analyses show that the inhibitory effect of the digital divide on energy transition is more significant in densely populated cities, economically and technologically developed cities, and non-resource-based cities. The above findings hold significant practical implications for overcoming the digital divide and the stagnation of energy transition, and for the scientific implementation of China’s “Carbon Neutrality” initiative.